Development of Cancer in Patients With Heart Failure: How Systemic Inflammation Can Lay the Groundwork - Ausoni, Simonetta; Azzarello, Giuseppe (Frontiers in Cardiovascular Medicine, 2020)
In the last decade, cardiologists and oncologists have provided clinical and experimental evidence that cancer, and not only chemotherapeutic agents, can cause detrimental effects on heart structure and function, a consequence that has serious clinical implications for patient management. In parallel, the intriguing idea that heart failure (HF) may be an oncogenic condition has also received growing attention. A number of epidemiological and clinical studies have reported that patients with HF have a higher risk of developing cancer. Chronic low-grade systemic inflammation has been proposed as a major pathophysiological process linking the failing heart to the multi-step process of carcinogenesis. According to this view, pro-inflammatory mediators secreted by the damaged heart generate a favorable milieu that promotes tumor development and accelerates malignant transformation. HF-associated inflammation synergizes with tumor-associated inflammation, so that over time it is no longer possible to distinguish the effects of one or the other. Experimental studies have just begun to search for the molecular effectors of this process, with the ultimate goal that of identifying mechanisms suitable for anti-cancer target therapy to reduce the risk of incident cancer in patients already affected by HF. In this review we critically discuss strengths and limitations of clinical and experimental studies that support a causal relationship between HF and cancer, and focus on HF-associated inflammation, cardiokines and their endocrine functions linking one and the other disease.